Feasibility Assessment of Basin Solar Stills - Agboola, O. Phillips; Atikol, U.; Assefi, Hossein (Taylor & Francis Inc, 2015)
The present study assesses the feasibility of exploiting single- and double-basin solar stills in our daily lives. An investigation is carried out to determine the thermal performance and economic viability of making use of solar stills in water desalination. The climatic conditions of Tehran (35 degrees 44MODIFIER LETTER PRIMEN, 51 degrees 30MODIFIER LETTER PRIMEE) are considered to assess the feasibility of the basins. Transient energy and mass balance equations are utilized for modeling the thermal performance. The equations are solved by using fourth-order Runge-Kutta method in FORTRAN. The daily productivities of single- and double-basin solar stills are found to be 5.22 kg/m(2) and 7.73 kg/m(2), respectively, while the effect of different water masses (20-100 kg) on the productivity of each system was found to be optimum at 20 kg/m(2). The results are compared with experimental work performed under different climatic conditions to examine the validity of the feasibility of basins in general. A life cycle cost analysis performed for Tehran, yields that single- and double-basin solar stills have savings-to-investment ratios of 4.2 and 4.8, respectively, indicating that they are economically feasible.
10th International Conference on Clean Energy -- SEP 15-17, 2010 -- Famagusta, CYPRUS
Keywords: Productivity analysis; Single and double basin; Economic analysis; Solar desalination